2019
DOI: 10.1039/c9tc03710a
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetic response in PbZr1−xTixO3 single crystals

Abstract: For the first time, a weak ferromagnetic hysteresis loop at room temperature has been observed in PbZr1−xTixO3 (PZT) single crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In contrast, when the poling is perpendicular to the O-Pb-O axis (Figure 11b), we obtain a spin-polarised defect state located at the two Ti atoms next to the two missing oxygen O rows. Such a weak magnetic response has already been observed in defected PZT single crystals [55]. The state is located at and in the conduction band minimum, making the system metallic (Figure 12).…”
Section: Dft Calculations and Source Of The Charge Carriers In Electr...supporting
confidence: 60%
“…In contrast, when the poling is perpendicular to the O-Pb-O axis (Figure 11b), we obtain a spin-polarised defect state located at the two Ti atoms next to the two missing oxygen O rows. Such a weak magnetic response has already been observed in defected PZT single crystals [55]. The state is located at and in the conduction band minimum, making the system metallic (Figure 12).…”
Section: Dft Calculations and Source Of The Charge Carriers In Electr...supporting
confidence: 60%
“…The first phase diagram for PbZr x Ti 1-x O 3 (PZT) solid solutions, which was proposed by Sawaguchi in 1953 [ 1 ], was derived only from measurements on ceramics. However, even now, nearly seven decades since the system’s discovery, only a few papers have reported the properties of PZT single crystals [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ], mainly because of the difficulties in the technology involved in their growth [ 10 ]. Ceramics are much easier to make, so most papers on PZT have been on ceramics, especially at compositions around the MPB region, PbZr 0.52 Ti 0.48 O 3 [ 11 ], where there is a boundary between ferroelectric rhombohedral (F R ) and ferroelectric tetragonal (F T ) phases, and where the large piezoelectric effect was found.…”
Section: Introductionmentioning
confidence: 99%
“…After more than six decades, solid solutions of PbZr 1−x Ti x O 3 (PZT) still continue to be intensively studied piezoelectric materials and are among the most interesting compounds from the application perspective. Recently, ferromagnetic properties were also found in a PZT crystal [1], which means that these materials can be classified as multiferroics and may find even wider application. For a long time, the PZT phase diagram developed by Jaffe et al [2] has been accepted as the basic characterization of the PZT solid solution.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 40 years ago, Whatmore et al [10] found that the diagram for ceramics differs from that for crystals. Only a few reports described the properties of PZT single crystals [1,[9][10][11][12][13][14][15][16], mainly due to above mentioned technological difficulties related to their growth. Our high quality single PbZr 0.87 Ti 0.13 O 3 crystal enabled investigations of phase transformations, domain structure, optical, dielectric, pyroelectric and elastic properties.…”
Section: Introductionmentioning
confidence: 99%